Influence of microfibrillated cellulose and soft biocomponent on the morphology and thermal properties of thermoplastic polyurethanes. Issue 37 (1st May 2021) - Panaitescu, Denis Mihaela; Nicolae, Cristian Andi; Melinte, Violeta; Scutaru, Andreea Laura; Gabor, Augusta Raluca; Popa, Marius Stelian; Oprea, Madalina; Buruiana, Tinca
Abstract: Composite materials from thermoplastic polyurethanes (TPUs) with biodegradable segments and microfibrillated cellulose (MFC) were developed as alternatives to traditional materials used in packaging or biomedical applications. Two TPUs were synthesized by the prepolymer method starting from different soft segments, poly(ε‐caprolactone)/poly(butylene adipate) (PUBA) or poly(ε‐caprolactone)/poly(ethylene oxide) (PUEO), and isophorone diisocyanate/aliphatic chain extender. Proton nuclear magnetic resonance ( 1 H NMR) confirmed the structure and Fourier transform infrared spectroscopy (FTIR) along with scanning electron microscopy showed that the soft segments with different hydrophobicity led to a higher phase mixing in PUBA and improved microphase separation in PUEO. MFC was added in the TPUs with different soft segments to increase biocompatibility, strength, and degradation rate. A better thermal stability, a gradual increase of crystallinity and a better dispersion of MFC were noticed in PUEO composites compared to PUBA ones. The crystallinity increased with 78% and 50% in PUBA and PUEO composites with 5 wt% MFC compared to the neat polyurethanes showing the nucleating ability of MFC. In addition, the enhanced storage modulus, with 75% and 25% in PUEO and PUBA composites, highlighted the reinforcing efficiency of MFC. Therefore, the addition of MFC to the already synthesized TPUs allows tailoring the morphology and thermal properties of TPUs for industrial application. Abstract :